Impact of intrinsic properties of foulants on membrane performance in osmotic desalination applications - Arkhangelsky, Elizabeth (2014)
This study investigates the effect of intrinsic physico-chemical properties of polysaccharides and proteins on the performance of flat sheet and hollow fiber forward osmosis (FO) membranes in different modes. Results showed that the foulant hydrodynamic diameter, zeta potential and rheological behavior were essential characteristics that govern the osmotic desalination processes. Diffusivity was the dominant mechanism governing the performance of hollow fiber membranes in FO mode, while the performance of flat sheet membrane in pressure retarded osmosis (PRO) mode was controlled by a combination of three mechanisms: diffusivity, size exclusion and electrostatic forces.